1999
DOI: 10.1021/ma980737x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Rheology and Light Scattering in Isotactic Polypropylene during Early Stages of Crystallization

Abstract: Structure development during crystallization of isotactic polypropylene (iPP) at low undercooling is studied by small-angle light scattering (SALS) and light transmission. The structure development is related to network formation (gelation) as previously measured on the same sample in dynamic mechanical experiments. Close to the rheologically measured gel point, small-angle light scattering (SALS) patterns in both Hv and Vv modes show circular symmetry; density fluctuations (maximum in Vv invariant) as determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
87
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 29 publications
20
87
2
Order By: Relevance
“…) corroborated the earlier observations, not only in PE but also in a variety of other polymers, such as iPP, 43,44,50,[52][53][54][55][56][57][70][71][72][73][75][76][77][78] isotactic poly-1-butene (iPB), 90 polyethylene terephthalate (PET), 91 polydiethylsiloxane (PEDS), 91 etc. In some report, the quasicrystallographic flowinduced structures are referred to as ''mesophase.''…”
supporting
confidence: 85%
See 1 more Smart Citation
“…) corroborated the earlier observations, not only in PE but also in a variety of other polymers, such as iPP, 43,44,50,[52][53][54][55][56][57][70][71][72][73][75][76][77][78] isotactic poly-1-butene (iPB), 90 polyethylene terephthalate (PET), 91 polydiethylsiloxane (PEDS), 91 etc. In some report, the quasicrystallographic flowinduced structures are referred to as ''mesophase.''…”
supporting
confidence: 85%
“…It was shown that a fraction of PE molecules adopted all-trans sequence configurations upon shearing, which remained stable for several hours even after cessation of shear. The recent results of the techniques that couple flow (parallel plate, [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]66,68,[74][75][76][77][78] fiber pullout, 14,79,80 die extrusion 15,[70][71][72][73][81][82][83] ) with a physical probe of the structure development (transmitted light, [70][71][72][73][81][82][83] optical microscopy, 14,[75][76][77][78]79,80 X-ray diffraction, 42-57 atomic force microscopy, …”
mentioning
confidence: 99%
“…Perhaps a network of physical crosslinks is formed (Boutahar et al 1996(Boutahar et al , 1998Coppola et al 2006;Peters et al 2002;Pogodina et al 1999a;Zuidema et al 2001). Subsequently, spherulites grow in this altered melt, the effect of which is well described by suspension-like behavior.…”
Section: Early Stage Of Crystallizationmentioning
confidence: 99%
“…Such an analysis provides information about large fluctuations in density and orientation and, accordingly, about the size and the perfection of the structures. 44 A dispersion diagram Hv with a four-leaf clover symmetry was attained. The average size estimated for the spherulites by polarized light microscopy was 4-9 µm of radius while it was 3-4 µm by SALS measurements.…”
Section: Structural Characterizationmentioning
confidence: 99%